The Accuracy of Salivary Protein Biomarkers for Detection of Oral Squamous Cell Carcinoma: A Systematic Review and Meta-analysis - Isipradit, Siraphop; Thaweedej, Sasithorn (Journal of The Department of Medical Services, 2021)
Background: There are various studies about salivary biomarkers in oral squamous cell carcinoma detection at the present. Many studies support that saliva may be considered as a promising for oral squamous cell carcinoma diagnosis and prognosis tool. Numerous studies also found that salivary protein biomarker yielded high sensitivity and high specificity.Objective: The systematic review and meta-analysis was to find out the accuracy of salivary protein biomarker in detection of oral squamous cell carcinoma.Methods: The following database were searched from 2000 to July 2020 from PubMed, google scholar and hand search.Results: Total of 15 studies which are prospective blinded trial, case-controlled studies, cross-sectional studies were included in this systematic review and meta-analysis. Sensitivity and specificity with 95% confidence interval are generated. The results showed pooled sensitivity of 0.78 (95% CI = 0.74, 0.82) and specificity of 0.71 (95% CI = 0.65, 0.76). ODD-ratio subgroup analysis was also generated in which the result showed that Cytokines salivary protein biomarker had higher ODD-ratio 11.41 (95% CI = 7.92, 16.45) compared to metalloproteinase salivary biomarkers 7.88 (95% CI = 5.72, 10.86) and other proteins salivary protein biomarker 5.55 (95% CI = 5.09, 6.10).Conclusion: Salivary protein biomarkers might not be sensitive and specific enough to serve as a detection tool of oral squamous cell carcinoma. Protein cytokines markers had high ODD-ratio but with its high wide range of confidence interval and low quality of studies, further studies of salivary protein biomarkers need to be developed.